Analysis of the Impact of Tax Incentives on Corporate In-vestment: An Empirical Study of Tax Holiday and Tax Al-lowance Policies in Indonesia for the 2022-2026 Period - Arda Raditya Tantra; Bulan Karima Nurani; Rina Setyowati (International Forum of Researchers and Lecturers, 2026)
This study examines the impact of tax incentive policies, specifically tax holidays and tax allowances, on corporate investment realization in Indonesia during the 2022-2026 period. Using a descriptive quantitative approach with secondary data from the Ministry of Investment and Downstream Industry/BKPM, the Fiscal Policy Agency of the Ministry of Finance, and the Central Statistics Agency (BPS), this research analyzes the relationship between tax expenditure and investment growth. The analysis reveals that investment realization grew from IDR 1,207.2 trillion in 2022 to IDR 1,931.2 trillion in 2025, representing an increase of 59.9 percent over three years. In the first quarter of 2026, investment realization reached IDR 498.8 trillion, growing 7.2 percent year-on-year, against an annual target of IDR 2,041.3 trillion. During the same period, tax expenditure directed at improving the investment climate rose from IDR 54.8 trillion to an estimated IDR 95.0 trillion. Tax holidays proved effective in attracting investors to mineral downstream sectors and special economic zones, while tax allowances contributed to labor-intensive and technology-driven investment. The study concludes that tax incentives positively contribute to corporate investment growth, though effectiveness is also shaped by legal certainty, infrastructure quality, and the implementation of the 15 percent global minimum tax from January 2025.